2009
DOI: 10.1158/1078-0432.ccr-09-1525
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in an Overweight or Obese Patient Is an Adverse Prognostic Factor in Pancreatic Cancer

Abstract: Purpose: The average weight-losing pancreatic cancer patient undergoing palliative therapy is frequently overweight rather than underweight, and this can confound conventional measures used for risk stratification. The aim of this study was to evaluate if weight and body composition, specifically sarcopenia, assessed from diagnostic computed tomography (CT) scans, is of prognostic value in patients with pancreatic cancer. The nature and extent of tissue loss over subsequent months was also evaluated. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
464
13
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(514 citation statements)
references
References 39 publications
26
464
13
11
Order By: Relevance
“…While TPA and BSA could significantly predict the development of acute radiation complications, BMI could not. BMI has been found to be a useful metric in outcomes related to obesity, and rarely has it found usefulness for low BMI (24,60). When dealing with a patient population that is generally underweight, we found no significant role for BMI regarding our selected outcomes.…”
Section: Discussionmentioning
confidence: 57%
“…While TPA and BSA could significantly predict the development of acute radiation complications, BMI could not. BMI has been found to be a useful metric in outcomes related to obesity, and rarely has it found usefulness for low BMI (24,60). When dealing with a patient population that is generally underweight, we found no significant role for BMI regarding our selected outcomes.…”
Section: Discussionmentioning
confidence: 57%
“…CT scan is the gold standard for quantifying skeletal muscle mass [22], and Mourtzakis et al [18] have shown that the CT cross sectional area at L3 is strongly related to appendicular skeletal mass, a common index of sarcopenia as measured by dual-energy X-ray densitometry. CT cross-sectional area at L3 single slice was employed in many studies as a reliable method to evaluate body composition [7,10,23]. In our study, mean SMI (cm 2 /m 2 ) decreased from 46.6 to 43.6 by 1 year after surgery and ATI (cm 2 /m 2 ) decreased from 76.4 to 21.4; these declines corresponded to 6.2 % and 65.8 % reductions of the preoperative values, respectively ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It leads to nosocomial infections [3], postoperative complications [4][5][6][7], increased length of hospital stay [7,8], and decreased survival in nonmalignant as well as malignant populations [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the influence of sarcopenia on treatment outcomes in cancer patients has been intensively investigated; sarcopenia was demonstrated to be independently associated with negative short-term [11][12][13][14][15][16][17][18] and long-term [11,[18][19][20] outcomes after surgery and an increased rate of chemotherapy-related toxicity [21][22][23].…”
Section: Introductionmentioning
confidence: 99%